Key technology of reconstructing WAN - Xiaojun GUO; Xiaolan WAN (Dianxin kexue)
There are many problems on traditional WAN,change is imperative,and it is very important to reconstruct WAN,which leads to software defined-wide area network (SD-WAN) reconstructing style.Among the current technology,the definition of SD-WAN,SD-WAN architecture,ODL open platform,protocol of control platform and southern protocol were analyzed and discussed.How to choose specific technology needs to combine technology maturity and application practice to decide.